2001
DOI: 10.1177/152660280100800408
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Polyester—Covered Stent in an Experimental Abdominal Aortic Aneurysm Model

Abstract: Spontaneous AAA rupture occurred earlier and was not as frequent as previously described for this model. Implantation of the covered stent was feasible, but aneurysm exclusion was not immediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Of the 46 selected studies, 30, 15, and 1 reported swine, ovine, and bovine data, respectively. 2 , 10 53 In the 1 paper we found describing bovine arterial dimensions, only thoracic aorta measurements were determined to be relevant in this study. We found no study describing aortic arch branch diameters in calves and only 1 study in sheep reporting brachiocephalic trunk diameters.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 46 selected studies, 30, 15, and 1 reported swine, ovine, and bovine data, respectively. 2 , 10 53 In the 1 paper we found describing bovine arterial dimensions, only thoracic aorta measurements were determined to be relevant in this study. We found no study describing aortic arch branch diameters in calves and only 1 study in sheep reporting brachiocephalic trunk diameters.…”
Section: Resultsmentioning
confidence: 99%
“…In all others, endothelization was incomplete. Some abdominal and iliac aorta models that have been described underwent endothelization 27 , 28 , while others had formation of neointima 29 , 30 . The different flow characteristics of the thoracic aorta, the interval between surgical intervention and data collection and the format of the aneurysm may be responsible for this variation.…”
Section: Discussionmentioning
confidence: 99%
“…The interposition graft model has been reproduced in dogs, pigs and sheep, with grafts made from crimped woven Dacron [93][94][95][96][97], biomedical grade elastomeric polyurethane [95], autologous jugular vein [98] or gastric serosa patches [99] and segments of glutaraldehyde-treated bovine internal jugular vein [100] to mimic an aneurysm. Another disadvantage is that these aneurysms do not show progressive enlargement thus differing from human AAAs [93][94][95][96][97][98][99][100]. A disadvantage of this model noted in all animals is the presence of moderate to severe fibrous reaction around the artificial aneurysm and in the sac wall.…”
Section: Interposition Graft Modelmentioning
confidence: 99%
“…polyurethane-coated expandable Nitinol stents with/without stainless steel frame [50,95], macroporous polyester-covered stents [98,183], Dacron-wrapped [184] or nylon-covered [185] selfexpanding metallic Gianturco stents, weft-knit Dacron tube with a balloon-expandable stents [94], tantalum-Dacron co-knit stents [96], etc.). polyurethane-coated expandable Nitinol stents with/without stainless steel frame [50,95], macroporous polyester-covered stents [98,183], Dacron-wrapped [184] or nylon-covered [185] selfexpanding metallic Gianturco stents, weft-knit Dacron tube with a balloon-expandable stents [94], tantalum-Dacron co-knit stents [96], etc.).…”
Section: Experimental Models For Endovascular Aaa Repair (Evar)mentioning
confidence: 99%